2014
DOI: 10.1115/1.4026919
|View full text |Cite
|
Sign up to set email alerts
|

Performance Prediction of Gel Water Shutoff in Horizontal Wells Using a Newly Coupled Reservoir–Wellbore Model

Abstract: Water shutojf is a commonly used method to mitigate the early breakthrough in horizontal wells. Gel is frequently used as an effective water shutoff agent in mature fields, especially for horizontal wells in recent years. However, the relevant water shutoff prediction model lacks the accurate physical description of the gelation phenomenon. Using the conventional model, which simply accounts for the gelation mechanisms, does not allow us to predict the horizontal wells performance correctly. In this paper, a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Though the techniques found merits in theory and laboratory tests, in field trials, most of them are found to be either ineffective or damaging. It is believed that, since gels are water-based solutions, they would preferentially enter high water-saturated zones (Chauveteau 2004;Xianchao et al 2014). However, in detail analysis, it is seen that the gelant penetration distances were not much different in high oil and high water-saturated zones (Liang et al 1993).…”
Section: Introductionmentioning
confidence: 95%
“…Though the techniques found merits in theory and laboratory tests, in field trials, most of them are found to be either ineffective or damaging. It is believed that, since gels are water-based solutions, they would preferentially enter high water-saturated zones (Chauveteau 2004;Xianchao et al 2014). However, in detail analysis, it is seen that the gelant penetration distances were not much different in high oil and high water-saturated zones (Liang et al 1993).…”
Section: Introductionmentioning
confidence: 95%
“…The existing coupled models simplify the gel blocking effects and do not capture the complete dynamic interactions involved. 153,157,158 Despite the availability of numerical simulation tools for designing water shutoff treatments, there exists a gap between prediction accuracy and field performance due to inadequate consideration of fluid composition and reservoir properties during the design and optimization stage. Consequently, this can significantly impact the efficiency of the treatment and, eventually, the project's economic viability.…”
Section: Pam Cross-linked With Nn′-methylenebis(acrylamide)mentioning
confidence: 99%
“…The current state-of-the-art in coupled modeling does not fully address or integrate these two key aspects. The existing coupled models simplify the gel blocking effects and do not capture the complete dynamic interactions involved. ,, …”
Section: Utilizing Nanomaterials For Enhancing Gel Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations